Chemical modulation of chloroplast de- and redifferentiation reveals a role for the SAL1–PAP retrograde pathway in facilitating plastid transitions - Pablo Perez-Colao; Jacobo Cruces; Santiago Perez-Rodriguez; Anna Koprivova; Stanislav Kopriva; Aleksandra Skirycz; Jorge Lozano-Juste; Manuel Rodriguez-Concepcion (Proceedings of the National Academy of Sciences, 2026)
Plastids are dynamic organelles that remodel their composition, ultrastructure, and function according to developmental and environmental demands. The synthetic molecule X57 induces the conversion of leaf chloroplasts into tocopherol-rich plastids lacking thylakoids and containing proliferating plastoglobules. Removal of X57 triggers chloroplast redifferentiation, enabling precise spatial–temporal dissection of these transitions. X57 directly binds and inhibits the phosphatase SAL1, causing accumulation of its substrate 3′-phosphoadenosine 5′-phosphate (PAP), a retrograde signal that modulates nuclear gene expression. SAL1 inhibition activates a cascade that depletes cytokinins and down-regulates GOLDEN2-LIKE1 (GLK1) and other transcription factors involved in chloroplast biogenesis. SAL1-defective mutants fail to undergo this signaling pathway. The SAL1–PAP–mediated weakening of chloroplast identity preconditions plastids for their eventual conversion into storage-type organelles upon X57-promoted SAL1-independent accumulation of tocopherols. After X57 withdrawal, photosynthetic gene expression and chloroplast functions are restored. This framework identifies key molecular mechanisms underlying chloroplast plasticity, a central process in biology.